Evaluation of an [(18)F]AlF-NOTA Analog of Exendin-4 for Imaging of GLP-1 Receptor in Insulinoma - Kiesewetter, Dale O. (Ivyspring International Publisher, 2012)
Introduction: The GLP-1 receptor plays an important role in glucose homeostasis and thus is a very important target for diabetes therapy. The receptor is also overexpressed in insulinoma, a tumor of pancreatic beta-cells. We previously evaluated two fluorine-18-labeled analogs of exendin-4 prepared by conjugation with [(18)F]FBEM (N-[2-(4-[(18)F]fluorobenzamide)ethyl]maleimide). Both compounds demonstrated good tumor uptake, but the synthesis of the radiotracers was time consuming. To overcome this challenge, we developed a NOTA analog and performed radiolabeling using aluminum [(18)F]fluoride complexation. Methods: Cys(40)-exendin-4 was conjugated with NOTA mono N-ethylmaleimide. [(18)F]AlF conjugation was conducted and the radiolabeled product purified by preparative HPLC. Dynamic and static PET imaging scans were conducted on nude mice with established INS-1 xenografts. Uptake of tumor and other major organs in static images was quantitated (%ID/g) and comparison with blocking studies was made. PET quantification was also compared with ex vivo biodistribution results. Results: The radiosynthesis provided [(18)F]AlF-NOTA-MAL-cys(40)-exendin-4 in 23.6 ± 2.4 % radiochemical yield (uncorrected, n = 3) after HPLC; the process required about 55 min. The specific activity at time of injection ranged from 19.6 to 31.4 GBq (0.53-0.85 Ci)/µmol. Tumor uptake had reached its maximum (16.09 ± 1.18% ID/g, n = 4) by 5 min and remained nearly constant for the duration of the study. Kidney uptake continued to increase throughout the entire one hour time course. Pre-injection of exendin-4 caused a marked reduction in tissue uptake with the major exception of liver and kidneys, in which uptake was not affected. HPLC analysis of the radioactive components in extracts of the tumor and plasma showed primarily parent compound at 60 min post-injection, whereas extracts of kidney and urine contained exclusively one polar radioactive component. Conclusion: The radiotracer is prepared in a simple one-step procedure and obtained in high specific activity after HPLC purification. [(18)F]AlF-NOTA-MAL-exendin-4 shows high tumor uptake and highly selective GLP-1 tissue uptake (INS-1 tumor, lung, pancreas), but still suffers from high kidney uptake.